Correlates of Role Enactment among the Academic Chairpersons of Selected Institutions in Bukidnon - Lalevie Lubos (Philippine Association of Institutions for Research, Inc., 2013)
The chairpersons' role and approaches to conflict management, strategies in communication and techniques in program implementation are enacted by the department Chairpersons. The study aimed to investigate the correlates of role performance of the chairpersons as perceived by the role incumbent and role partners. The study used the descriptive design involving the incumbent deans, department chairpersons and faculty members of the HEIs. The study utilized the non-probability sampling design .The mean, standard deviation, ANOVA, and Pearson correlation were used. Results showed that the level of role conception of academic chairpersons within the same range as that of the role enactment as perceived by the deans and their role partners (faculty). The approaches to conflict management, strategies in communication and techniques in program implementation are correlates of administrative role, leadership role, interpersonal role, resource development role, role enactment of academic chairpersons. The study concludes that the chairpersons' level of role conception in their administrative roles, leadership roles, interpersonal roles and resource development roles is congruent with their perceived role enactment as assessed by the deans and faculty. The extent chairpersons used approaches to conflict management, strategies to communication and techniques in program implementation determines the adequacy of role enactment of academic chairpersons as they perform.